2003
DOI: 10.1007/978-3-540-39964-3_82
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Concerns of Distributed Deployment and Dynamic Composition in Internet Application Systems

Abstract: Abstract. The Internet is currently evolving from a global information network into a distributed application system. For example, some Internet applications are based on executing remote services which have been previously installed on possibly multiple Internet nodes, whereas parts of other Internet applications are dynamically moved from several remote nodes to be executed on a single node. In this paper, we focus on the related problem of how the parts of an Internet application that have been independentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite the important role that software technology is playing in the development of (distributed) control systems, it has been reported that the In contrast, [33] reports on a framework targeting similar applications as our own does but based on CORBA. Harinath et al [34] describes an object-oriented framework, also for control applications, based on the use of COTS components. In a more general setting, [35] describes an open framework for multimedia services where they use the notion of coordination in terms of connectors which encapsulate the coordination aspects and components dealing with the computational aspects (in contrast, we also highlight the coordination and computation separation but in terms of a specialized component along with specific sub-components within the major component units of our framework).…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…Despite the important role that software technology is playing in the development of (distributed) control systems, it has been reported that the In contrast, [33] reports on a framework targeting similar applications as our own does but based on CORBA. Harinath et al [34] describes an object-oriented framework, also for control applications, based on the use of COTS components. In a more general setting, [35] describes an open framework for multimedia services where they use the notion of coordination in terms of connectors which encapsulate the coordination aspects and components dealing with the computational aspects (in contrast, we also highlight the coordination and computation separation but in terms of a specialized component along with specific sub-components within the major component units of our framework).…”
Section: Related Work and Discussionmentioning
confidence: 99%